2006
DOI: 10.1128/mmbr.00016-06
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Gene Regulation in the Bacterial World

Abstract: SUMMARY Like many eukaryotes, bacteria make widespread use of postreplicative DNA methylation for the epigenetic control of DNA-protein interactions. Unlike eukaryotes, however, bacteria use DNA adenine methylation (rather than DNA cytosine methylation) as an epigenetic signal. DNA adenine methylation plays roles in the virulence of diverse pathogens of humans and livestock animals, including pathogenic Escherichia coli, Salmonella, Vibrio, Yersinia, Haemophilus, and Brucella. In Alphaproteob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
582
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(588 citation statements)
references
References 306 publications
(391 reference statements)
3
582
0
3
Order By: Relevance
“…Despite the absence of cognate REases, orphan MTases still confer immunity against the virulence of a parasitic R-M complex with the same target sites (9). In addition to defense against bacteriophages and transposons, DNA methylation is involved in various cellular functions, including chromosome replication, DNA mismatch repair, transcriptional regulation, transposition, and pathogenesis (1,10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the absence of cognate REases, orphan MTases still confer immunity against the virulence of a parasitic R-M complex with the same target sites (9). In addition to defense against bacteriophages and transposons, DNA methylation is involved in various cellular functions, including chromosome replication, DNA mismatch repair, transcriptional regulation, transposition, and pathogenesis (1,10,11).…”
mentioning
confidence: 99%
“…DNA phosphorothioation | DNA methylation | epigenetics | restriction-modification | bioanalytical chemistry T he emergence of convergent technologies has led to a growing appreciation for the diversity of DNA modifications in microbial epigenetics and restriction-modification (R-M) systems (1)(2)(3). DNA methylation, the most extensively studied genetic modification, was originally discovered in bacteria in the context of R-M systems involving a methyltransferase (MTase) that modifies "self" DNA at specific target sites and a cognate restriction endonuclease (REase) that discriminates and destroys unmodified invading DNA (3)(4)(5).…”
mentioning
confidence: 99%
“…Bacteria use DNA methylation (of adenine and of cytosine) both as a primitive immune system through restrictionmodification and to provide signals for DNA replication, mismatch repair and transcription [3]. For example, DNA methylation controls the heritable expression of Pyelonephritis-associated pili (Pap) [4].…”
Section: Gene Switching and Silencing In Prokaryotesmentioning
confidence: 99%
“…Pap are hair-like appendages that play a role in attachment of bacteria to cells lining the mammalian urinary tract, facilitating colonisation of the kidneys. Expression of the genes controlling pili production is either ON or OFF in any individual cell of the population [3]. The switch rate is low (and, as far as we know, stochastic) so most, but not all, daughter cells acquire the same state as the parent cell.…”
Section: Gene Switching and Silencing In Prokaryotesmentioning
confidence: 99%
“…Unlike most bacterial methyltransferases, EcoDam does not belong to a restriction-modification system that serves to protect the cell from foreign DNA. Instead, the methylation by EcoDam of the ϳ20,000 GATC sites within the E. coli genome is critical in a number of biological pathways including gene regulation, chromosome replication, mismatch repair, and nucleoid structure determination (11,12). It has been shown that there are relatively few EcoDam molecules per bacterial cell suggesting that high processivity is essential in the methylation of the large number of GATC sites in the E. coli genome to avoid hyper-mutating phenotypes (10,11,13).…”
mentioning
confidence: 99%